OPTIMIZING KNOWLEDGE MANAGEMENT IN THE STRATEGY TO ENHANCE THE VALUE AND COMPETITIVE ADVANTAGE OF INBYCLOTHING THRIFTING IN TANJUNGBALAI - Aditya Rahma Dani Hasibuan; Mutmainnah Mutmainnah; Nurmala J unanda; Vivi Elvia Rahayu; Nurhasanah Nurhasanah (Smart Education, 2025)
Abstrak: This research aims to analyze the implementation of Knowledge Management through the SECI model conversion framework in enhancing the business competitiveness of the thrift store Inbyclothing in Tanjungbalai City. The research method applied is a qualitative case study utilizing in-depth interviews and field observations. The results indicate that the implementation of the SECI model plays a vital role in transforming the owner's tacit knowledge into a collective corporate asset. The utilization of Standard Operating Procedures (SOP) for international retail brand curation alongside active TikTok live streaming activities is proven successful in improving product quality, national market reach, and sales. A consistent knowledge conversion strategy is capable of shifting business operations from being owner-dependent to becoming driven by structured workflow standardization. This study demonstrates that effective knowledge management can serve as a key strategy for thrifting MSMEs to sustain a competitive advantage in the digital era. Keywords: SECI; Thrift; Product; Knowledge Management; Business Abstract: Penelitian ini bertujuan menganalisis pengimplementasian Manajemen Pengetahuan (Knowledge Management) melalui kerangka konversi Model SECI dalam meningkatkan daya saing bisnis thrift Inbyclothing di Kota Tanjungbalai. Metode penelitian yang digunakan adalah studi kasus kualitatif melalui wawancara mendalam dan observasi lapangan. Hasil penelitian menunjukkan bahwa pengimplementasian Model SECI memiliki peran penting dalam mentransformasikan pengetahuan tersirat (tacit) pemilik menjadi aset kolektif perusahaan. Penggunaan SOP kurasi merek retail internasional serta aktivitas live streaming TikTok secara aktif terbukti berhasil meningkatkan kualitas produk, jangkauan pasar nasional, dan penjualan. Strategi konversi pengetahuan yang konsisten mampu mengubah operasional bisnis dari ketergantungan pada figur pemilik (owner-dependent) menjadi berbasis standardisasi alur kerja yang terstruktur. Penelitian ini membuktikan bahwa manajemen pengetahuan yang efektif dapat menjadi strategi kunci bagi UMKM thrifting untuk mempertahankan keunggulan kompetitif di era digital. Kata kunci: SECI; Thrift; Produk; Manajemen Pengetahuan; Bisnis